Effect of environmental aging conditions on the properties of fly ash filled epoxy composites. (2nd January 2020) - Pattanaik, A.; Mukharjee, M.; Mishra, S.C.
Abstract : The effect of environmental aging conditions on the structural and mechanical properties of fly ash (FA) filled epoxy composites with four different volume fraction of FA (i.e. 0.1, 0.2, 0.3 and 0.4) has been investigated under four aggressive aging environments and aging periods. The crystallite size and microstrain of crystalline particle in the composite matrix is quantified from XRD analysis. The 10% FA filled epoxy composite under fuel solution retains the higher order of crystallinity and glass transition temperature. It is observed that the void content and actual density of composites decreases with increasing FA content. The mechanical behavior of FA epoxy composite deteriorated with increasing aging duration and reinforcement percentage. 10% FA-containing specimen gives the highest mechanical properties under fuel environment for any given aging duration. The 20% FA filled epoxy composite can also be used in low load bearing applications.